2012
DOI: 10.1093/ntr/nts030
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Characteristics and Comorbidities in the Power To Quit Randomized Clinical Trial for Homeless Smokers

Abstract: in emergency shelters; nearly half had been homeless for more than a year. Nearly all the participants were daily smokers who smoked an average of 20 cigarettes/day. Nearly 40% had patient health questionnaire-9 depression scores in the moderate or worse range, and more than 80% screened positive for lifetime history of drug abuse or dependence. Conclusions:This study demonstrates the feasibility of enrolling a diverse sample of homeless smokers into a smoking cessation clinical trial. The uniqueness of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…Smoking cessation interventions for homeless adults have focused on behavioral counseling and pharmacotherapy [3]. Although such therapy has been shown to have increased effectiveness when combined with smoke-free policies [4], no interventions have targeted smoke-free policies in homeless service settings.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking cessation interventions for homeless adults have focused on behavioral counseling and pharmacotherapy [3]. Although such therapy has been shown to have increased effectiveness when combined with smoke-free policies [4], no interventions have targeted smoke-free policies in homeless service settings.…”
Section: Introductionmentioning
confidence: 99%
“…33 Given these findings, there is mounting evidence for the integration of treatment for nicotine dependence with that of substance use treatment. 1,12,31,34 A meta-analysis showed that treating nicotine addiction during substance use treatment may enhance short-term smoking cessation and lead to prolonged abstinence from alcohol and other illicit substances. 34 Lower cigarette consumption and prior quit attempts were associated with increased likelihood of a subsequent quit attempt at Percentage represents column percentage among those who had made a quit attempt in the past 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on tobacco use in the homeless population has focused on younger adults, where the average age of study participants in previous studies was less than 44 years. 1,2,12,13 The high prevalence of tobacco use and the increased burden of tobacco-related chronic diseases with aging underscore a need for studies that characterize tobacco use and cessation behaviors among older homeless adults in order to develop tobacco control interventions that address the unique needs of this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 To gauge the social aspects of smoking, we asked participants how many of their five closest associates smoke cigarettes 41 and how many times they are offered a cigarette during a typical day. 42 …”
Section: Tobacco Usementioning
confidence: 99%